Optimization of a polarizer based on a square waveguide with irises - Булашенко, Андрій Васильович; Пільтяй, Степан Іванович; Демченко, Іван Вольдемарович (Science-based technologies, 2020)
Antenna systems with polarization signal processing are key element of modern satellite telecommunications systems. In such systems polarization processing is performed by waveguide polarizers. Thus, the development of the design of new polarizers, the creation of new methods for their analysis and optimization are important problems. Waveguide polarizers with irises are the most efficient and technologically advanced in manufacturing. Moreover, they provide wide bandwidths. Optimization of the electromagnetic characteristics of a waveguide polarizer with irises is the goal of the study. To achieve this purpose, we solve the problem to create a new mathematical model, which makes it possible to analyze the influence of the polarizer design parameters on its electromagnetic characteristics. In the investigation a model of a waveguide polarizer with irises was created using the theory of microwave circuits. A new analytical model of such a polarizer has been developed using a general wave scattering matrix. The main characteristics of the waveguide polarizer were determined through the matrix elements. In this work the optimization of characteristics of a polarizer based on a square waveguide with irises has been carried out in Ku-band 10.7–12.8 GHz. The presented mathematical model of such a polarizer allows to take into account the heights of the irises, the distances between them and their thicknesses. The results obtained show that the proposed model is simpler for calculation of the electromagnetic characteristics in comparison with the finite integration technique, which is used to analyze microwave devices for various purposes.